2003
DOI: 10.1007/s00414-003-0405-4
|View full text |Cite
|
Sign up to set email alerts
|

Complete detachment of an aortic valve prosthesis 10 years after implantation

Abstract: A 47-year-old male patient died unexpectedly 10 years after replacement of the aortic valve with a Carbomedics heart valve prosthesis required for post-endocarditic valve stenosis. The man was in regular medical attendance by his general practitioner and in hospital. Clinical data and examinations did not suggest the reoccurrence of endocarditis. Three months before his death a haemolytic anaemia of unknown genesis was diagnosed. One afternoon, while lifting a heavy object, the man suffered acute chest pain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Although complete detachment of valve prosthesis was reported in an autopsy case that was complicated by infective endocarditis [ 7 ], complete detachment of bileaflet mechanical aortic valve prosthesis in patients with Behçet’s disease has never been reported. Behçet’s disease is known to be typically associated with HLA-B51, however, a previous study showed that HLA-B51 positive did not result in frequent manifestations or severe disease course [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although complete detachment of valve prosthesis was reported in an autopsy case that was complicated by infective endocarditis [ 7 ], complete detachment of bileaflet mechanical aortic valve prosthesis in patients with Behçet’s disease has never been reported. Behçet’s disease is known to be typically associated with HLA-B51, however, a previous study showed that HLA-B51 positive did not result in frequent manifestations or severe disease course [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the critical situation, it is important to recognise the absence of the prosthetic valve with echocardiography or identify the embolised valve at the different position by chest X-ray. One of the most common causes of embolisation is prosthetic valve endocarditis, which can occur even at 10 years after prosthetic valve replacement 1 . P. acnes is reported to cause life-threatening endocarditis with prosthetic valve embolisation 2.…”
Section: Answer: Dmentioning
confidence: 99%